One step synthesis of high efficiency nickel/mesoporous TiO2 hybrid catalyst for hydrogen evolution reaction - Franceschini, Esteban Andrés (2019)
Nickel-TiO2 hybrid catalysts are synthesized by electrodeposition and their catalytic activity with respect to the hydrogen evolution reaction is analyzed. Two types of titanium oxide particles, which are commercial particles of dense TiO2 and mesoporous TiO2 particles synthesized by an aerosol method, are incorporated into the matrix of the nickel catalyst. Both nickel catalysts containing TiO2 particles presented higher catalytic activity than the conventional nickel Watts catalyst. Mesoporous TiO2-modified nickel catalyst showed the highest catalytic activity towards HER in alkaline medium. In addition, this type of nickel catalyst increases its catalytic activity after ageing treatment, which is an indication of an increase in the electro-active area of the electrode.